Smoking cessation advice recorded during pregnancy in United Kingdom primary care - Hardy, Bethany; Szatkowski, Lisa; Tata, Laila J.; Coleman, Tim; Dhalwani, Nafeesa (BioMed Central, 2014)
Background: United Kingdom (UK) national guidelines recommend that all pregnant women who smoke should be advised to quit at every available opportunity, and brief cessation advice is an efficient and cost-effective means to increase quit rates. The Quality and Outcomes Framework (QOF) implemented in 2004 requires general practitioners to document their delivery of smoking cessation advice in patient records. However, no specific targets have been set in QOF for the recording of this advice in pregnant women. We used a large electronic primary care database from the UK to quantify the pregnancies in which women who smoked were recorded to have been given smoking cessation advice, and the associated maternal characteristics. Methods: Using The Health Improvement Network database we calculated annual propotions of pregnant smokers between 2000 and 2009 with cessation advice documented in their medical records during pregnancy. Logistic regression was used to assess variation in the recording of cessation advice with maternal characteristics. Results: Among 45,296 pregnancies in women who smoked, recorded cessation advice increased from 7% in 2000 to 37% in 2004 when the QOF was introduced and reduced slightly to 30% in 2009. Pregnant smokers from the youngest age group (15–19) were 21% more likely to have a record of cessation advice compared to pregnant smokers aged 25–29 (OR 1.21, 95% CI 1.10-1.35) and pregnant smokers from the most deprived group were 38% more likely to have a record for cessation advice compared to pregnant smokers from the least deprived group (OR 1.38, 95% CI 1.14-1.68). Pregnant smokers with asthma were twice as likely to have documentation of cessation advice in their primary care records compared to pregnant smokers without asthma (OR 1.97, 95% CI 1.80-2.16). Presence of comorbidities such as diabetes, hypertension and mental illness also increased the likelihood of having smoking cessation advice recorded. No marked variations were observed in the recording of cessation advice with body mass index. Conclusion: Recorded delivery of smoking cessation advice for pregnant smokers in primary care has increased with some fluctuation over the years, especially after the implementation of the QOF, and varies with maternal characteristics.